Effectiveness of DNA barcoding markers in the description of a new and unusual calyptrate species of Myrcianthes (Myrtaceae) - Parra-O., Carlos; Bohórquez-Osorio, A. F. (Phytotaxa, 2016)
A new species, Myrcianthes roncesvallensis is described and illustrated from Andean forests of Tolima, Colombia. Due to the unusual combination of morphological characters in this new species never been found previously in a Colombian Myrtaceae, such as having a closed calyx, dichasial inflorescence and an eugenioid embryo, three DNA barcoding markers (rbcL, matK and ITS) were used to confirm the genus in which this species should be described. Taxonomic affinities of the new species within the genus are discussed.